2020
DOI: 10.3390/medicina56090445
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in Autoimmune Rheumatic Diseases for Diagnosis and Prognosis of Cardiovascular Complications

Abstract: Autoimmune rheumatic diseases are systemic diseases frequently affecting the heart and vessels. The main cardiovascular complications are pericarditis, myocarditis, valvular disease, obstructive coronary artery disease and coronary microcirculatory dysfunction, cardiac failure and pulmonary hypertension. Echocardiography, including transthoracic two and three-dimensional echocardiography, Doppler imaging, myocardial deformation and transesophageal echo, is an established and widely available imaging technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Several studies have demonstrated the effectiveness of novel echocardiography techniques (Tissue Doppler Imaging), especially global longitudinal strain through speckle monitoring, in assessing subclinical cardiac involvement and left ventricular diastolic dysfunction [ 5 ]. ECHO is a primary tool for detecting CV involvement, and it also assists in monitoring the therapeutic effects and disease progression [ 1 ]. A noninvasive method for detecting ATS plaques in the carotid artery is carotid ultrasound investigation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the effectiveness of novel echocardiography techniques (Tissue Doppler Imaging), especially global longitudinal strain through speckle monitoring, in assessing subclinical cardiac involvement and left ventricular diastolic dysfunction [ 5 ]. ECHO is a primary tool for detecting CV involvement, and it also assists in monitoring the therapeutic effects and disease progression [ 1 ]. A noninvasive method for detecting ATS plaques in the carotid artery is carotid ultrasound investigation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune-inflammatory rheumatic diseases (ARDs) are a group of systemic immune-mediated disorders with the potential to target various joints, bones, and connective tissues [ 1 ]. They are also correlated with a higher risk of developing cardiovascular diseases (CVD) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to assessing cardiovascular risk, CACS calculation also makes it possible to select more precisely those patients who need to be investigated with stress tests for silent myocardial ischemia [ 2 , 15 ]. We chose to use trans-thoracic echocardiography combined with ECG-coupled stress echocardiography because these imaging examinations are non-invasive and enable the researcher to visualize cardiac pathologies other than coronary artery disease, as seen in autoimmune diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ajeganova et al showed in a 10-year case-control-study, that SLE patients had a three- to four-fold higher risk of CV events and death, compared with persons who do not have SLE but with a similar pattern of traditional CVD risk factors and subclinical atherosclerosis measured with carotid intima-media thickness and presence of carotid plaque ( 36 ). A significantly improved prediction of the adverse outcome could be accomplished with the combination of cIMT measures with the Systemic Lupus International Collaborating Clinics (SLICC) Damage Index and coexistence of SLE-antiphospholipid syndrome (SLE-APS) ( 37 ). These findings highlight the necessity of a comprehensive approach to risk stratification and management.…”
Section: Cardiovascular Imaging: Detecting Subtle Changesmentioning
confidence: 99%
“…Echocardiography has found its way into routine preventative care in patients with autoimmune and rheumatological diseases, as the presence of cardiac abnormalities, such as heart muscle damage, pericardial involvement and valvular heart disease are relatively common. However, early structural, and functional changes are often subtle and not easy to detect ( 37 ). Therefore, conventional echocardiographic parameters may often be not sufficient to find these early abnormalities of cardiac dysfunction especially if the global ventricular function is normal.…”
Section: Cardiovascular Imaging: Detecting Subtle Changesmentioning
confidence: 99%